2016
DOI: 10.1111/bjh.14401
|View full text |Cite
|
Sign up to set email alerts
|

Whole body magnetic resonance imaging in newly diagnosed multiple myeloma: early changes in lesional signal fat fraction predict disease response

Abstract: SummaryCross‐sectional imaging techniques are being increasingly used for disease evaluation in patients with multiple myeloma. Whole body magnetic resonance imaging (WB‐MRI) scanning is superior to plain radiography in baseline assessment of patients but changes following treatment have not been systematically explored. We carried out paired WB‐MRI scans in 21 newly diagnosed patients prior to, and 8‐weeks after, starting chemotherapy, and analysed stringently selected focal lesions (FLs) for parametric chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 44 publications
0
40
0
2
Order By: Relevance
“…МРТ -широко распространенный метод исследования, не связанный с лучевой нагрузкой и требующий меньших временных и финансовых затрат, чем ПЭТ/КТ. В последние годы активно изучаются возможности новых режимов МРТ, в частности режим диффузионно-взвешенного изображения [19,20], использование которого позволяет определить не только объем опухоли, но и активность выявленных изменений МР-сигнала от костного мозга.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…МРТ -широко распространенный метод исследования, не связанный с лучевой нагрузкой и требующий меньших временных и финансовых затрат, чем ПЭТ/КТ. В последние годы активно изучаются возможности новых режимов МРТ, в частности режим диффузионно-взвешенного изображения [19,20], использование которого позволяет определить не только объем опухоли, но и активность выявленных изменений МР-сигнала от костного мозга.…”
Section: Discussionunclassified
“…Магнитно-резонансная томография (МРТ) -высокочувствительный метод определения поражения костного мозга при ММ [19][20][21][22][23][24]. В ряде исследований отмечалось негативное влияние на показатели выживаемости больных ММ измененного МР-сигнала от костного мозга [25][26][27]…”
Section: клиническая онкогематологияunclassified
“…52 A recent study reported that early signal fat fraction changes 8 weeks post-chemotherapy was a biomarker for inferior response. 60 Responders had a significant increase in signal fat fraction as the normal fat signal returned, whilst non-responders had no significant change.…”
Section: Response Assessmentmentioning
confidence: 92%
“…However, the consensus statement itself was evidence level D (panel consensus). Indeed, there have been only a few small studies evaluating the diagnostic performance of WB-MRI in response assessment [19][20][21][22][23], and, surprisingly, no study has evaluated the role of WB-MRI in differentiating progressive disease (PD) from non-PD, which is one of the most important issues in clinical oncology.…”
Section: Introductionmentioning
confidence: 99%